Multiway principal component analysis contributions for structural damage localization. (September 2018) - Ruiz, Magda; Mujica, Luis Eduardo; Sierra, Julián; Pozo, Francesc; Rodellar, José
In this article, a novel methodology for damage localization is introduced. The approach is based on a multiactuator system. This means that the system itself has the ability of both exciting the specimen and measuring its response at different points in a pitch-catch mode. Once one of its actuators excites the specimen, the damage affects the normal travel of the guided wave, and this change is mainly detected by sensors in the direct route to the excitation point. In previous works by the authors, it can be observed that the progression using data-driven statistical models (multivariable analysis based on principal component analysis) of all recorded signals to determine whether the damage is present. However, the main contribution of this article is the demonstration of the possibility of localizing damages by analyzing the contribution of each sensor to this index which have detected it ( T 2 -statistic and Q -statistic). The proposed methodology has been applied and validated on an aircraft turbine blade. The results indicate that the presented methodology is able to accurately locate damages, analyzing the record signals from all actuation phases and giving a unique and reliable region.